1989
DOI: 10.1007/bf01718026
|View full text |Cite
|
Sign up to set email alerts
|

Fehlender nächtlicher Blutdruckabfall in der 24-Stunden Blutdruckmessung: Hinweis auf eine sekundäre Hypertonie

Abstract: Non invasive 24 hours ambulatory blood pressure monitoring was performed in 81 patients with secondary hypertension (renoparenchymatous nephropathy n = 15, diabetic nephropathy n = 10, Conn's disease n = 4, renal artery stenosis n = 15, pheochromocytoma n = 2, hemodialysis patients n = 15 and patients after kidney transplantation n = 20). The results were compared to 201 patients with essential hypertension. The results showed that 98.5% of patients with essential hypertension have a nightly decline in blood p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

1990
1990
2003
2003

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…Patients who do not have a nocturnal BP drop are at greater risk for left ventricular hypertrophy [Verdecchia et al, 1990] and stroke [O'Brien et al, 1988]. Most patients with essential hypertension exhibit a nocturnal decrease in BP [Mallion et al, 1990] whereas this is lost in a number of disease states [Imai et al, 1988;Redman et al, 1976;Schrader et al, 1989].…”
Section: Discussionmentioning
confidence: 99%
“…Patients who do not have a nocturnal BP drop are at greater risk for left ventricular hypertrophy [Verdecchia et al, 1990] and stroke [O'Brien et al, 1988]. Most patients with essential hypertension exhibit a nocturnal decrease in BP [Mallion et al, 1990] whereas this is lost in a number of disease states [Imai et al, 1988;Redman et al, 1976;Schrader et al, 1989].…”
Section: Discussionmentioning
confidence: 99%
“…95% CL = Mean ± 95% CI [1] In addition, the spreadsheet was programmed to treat the rows in numerical order to compute in each individual BP series the following conventional estimates: daily mean (from 00.00 h to 24.00 h), diurnal mean (from 07.00 h to 23:00 h) and nocturnal mean (from 23.00 h to 07.00 h) [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] 60+ ALL …”
Section: Discussionmentioning
confidence: 99%
“…50 It must be stressed that the identification of a patient affected by 'aperiodic hypertension' is of clinical relevance in that it has been demonstrated that hypertensives who lack a periodicity in their 24-h BP values more often than not are suffering from secondary forms of high BP. [51][52][53][54][55][56][57][58][59][60] Therefore, the identification of the aperiodic chronotype should alert clinicians to the necessity for clinical and laboratory tests in order to discover the etiology of the hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Dies sind vor allem Patienten mit sekund/iren Hypertonieformen, mit Schwangerschaftshypertonie oder mit kardialen oder renalen Hochdruckfolgesch/iden [2,8,27,44,50,51]. Dies sind vor allem Patienten mit sekund/iren Hypertonieformen, mit Schwangerschaftshypertonie oder mit kardialen oder renalen Hochdruckfolgesch/iden [2,8,27,44,50,51].…”
Section: Fehlender N~ichtlicher Blutdruckabfallunclassified